Kepastian Hukum Pajak Kendaraan Bermotor dan Alat Berat di Kawasan Industri - Setiawan, Viko; Anwar, Muhamad Sholihul; Setiadi, Mochammad Adi; Putra, Jaffa Rizqita; Fitriyanti, Fitriyanti; Malika, Aliya (CV. ULIL ALBAB CORP, 2026)
This article aims to analyze legal certainty regarding the imposition of Motor Vehicle Tax (PKB) and Heavy Equipment Tax (PAB) in Southeast Sulawesi Province, particularly for companies operating in industrial zones. The main issue lies in the legal vacuum concerning the definition of “road” in Law No. 1 of 2022 on Fiscal Relations between Central and Regional Governments, which creates multiple interpretations of PKB objects. The research method applies a normative approach with grammatical interpretation of statutory regulations and a case study on smelter industry companies. The findings indicate that motor vehicles used on private industrial roads are not subject to PKB, while heavy equipment used as industrial production machinery is not subject to PAB. The conclusion emphasizes the necessity of harmonizing statutory regulations to prevent taxpayer losses and uphold the principle of legal certainty.